Differences in Crenate Broomrape Parasitism Dynamics on Three Legume Crops Using a Thermal Time Model - Pérez-de-Luque, Alejandro; Flores, Fernando; Rubiales, Diego (Frontiers in Plant Science, 2016)
Root parasitic weeds are a major limiting production factor in a number of crops, and control is difficult. Genetic resistance and chemical control lead the fight, but without unequivocal success. Models that help to describe and even predict the evolution of parasitism underground are a valuable tool for herbicide applications, and even could help in breeding programs. Legumes are heavily affected by Orobanche crenata (crenate broomrape) in the Mediterranean basin. This work presents a descriptive model based on thermal time and correlating growing day-degrees (GDD) with the different developmental stages of the parasite. The model was developed in three different legume crops (faba bean, grass pea and lentil) attacked by crenate broomrape. The developmental stages of the parasite strongly correlated with the GDD and differences were found depending on the host crop.